Temporal and Spatial Variation in Scots Pine Resin Pressure and Composition - Rissanen, Kaisa; Hölttä, Teemu; Barreira, Luís F. M.; Hyttinen, Noora; Kurtén, Theo; Bäck, Jaana (Frontiers in Forests and Global Change, 2019)
Resin is a first-line defense in pine trees, but important questions regarding its temporal and spatial variation remain unsolved. Resin pressure varies according to water potential in dry conditions, but in moist conditions, it follows temperature dynamics for a yet unknown reason. Relations between resin composition, resin pressure, and shoot monoterpene emissions are also unquantified. To gain mechanistic understanding on the resin dynamics in a boreal forest, we measured temperature and water potential dependency of Scots pine resin pressure. We attempted to quantify the temperature dependency of resin pressure in terms of three contributions: 1) saturation vapor pressure, 2) thermal expansion, and 3) N2, O2, and CO2 solubility. We also analyzed monoterpene composition in the resin and the shoot emissions of 16 pines with gas chromatography mass spectrometry to study their interrelations. We show that in moist conditions, resin pressure is driven by temperature at a diurnal scale, but also affected by soil water potential at a day-to-day scale. Diurnal temperature dependency was explained by thermal expansion of resin and changes in bubble volume due to changes in gas solubility in resin with temperature. Resin pressures correlated also with total monoterpene and α-pinene content in resin and with total monoterpene and ∆3-carene and terpinolene emissions from shoots.